(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article presents a comparative study of aphorisms in English and Uzbek through the analysis of corpus data. Aphorisms, as concise expressions of universal truths and cultural wisdom, serve as an essential part of linguistic and cultural heritage. The study explores the structural, semantic, and cultural features of aphorisms, focusing on how they are presented and used in both languages. By examining a balanced corpus of English and Uzbek aphorisms, the research identifies common patterns, unique linguistic devices, and culturally specific elements embedded within these expressions. The analysis highlights both universal tendencies in aphoristic expression and language-specific differences shaped by cultural and historical contexts. Furthermore, the paper discusses translation challenges and the role of aphorisms in intercultural communication. The findings contribute to a deeper understanding of the linguistic nature of aphorisms and offer insights for translation studies, intercultural pragmatics, and corpus linguistics.